Serum factors that suppress cytotoxic effect of methotrexate - Kojima, T.; Hashimoto, Y.; Inamura, Y.; Koide, T.; Nagata, H.; Ito, N.; Suzumura, K. (Experimental Oncology, 2009)
To study the phenomenon that human erythroid leukemia K-562 cells are more sensitive to cytotoxic effect of antimetabolites when cultured in a serum-free medium than in a conventional medium containing fetal calf serum (FCS). Methods: Cytotoxic effects of methotrexate, azaserine and 5-fluorouracil were estimated by accessing the lactate dehydrogenase (LDH) activity of viable tumor cells. Proteins of FCS were separated using two-dimensional electrophoresis followed by mass spectrometry analysis. Results: Addition of 10% FCS attenuated anti-tumor activity of methotrexate and azaserine against K-562 cells compared with serum-free medium. Such an activity of FCS was different for each serum lot. Comparison of the proteins in active serum lot with those in not active one using two-dimensional electrophoresis showed that in the active serum there were proteins 150 kDa, which were absent in the not active serum lot. Mass spectrometry indicated that all those proteins had the amino acid sequence of albumin. Sera of one healthy volunteer and two patients with thyroid cancer also attenuated the activity of the agent. Conclusion: Several lots of FCS and human serum demonstrated the ability to attenuate the cytotoxic effect of methotrexate in vitro, possibly due to the formation of albumin dimers/MTX complexes.